Base saturation for coffee plantations stablished according to soil ph and Ca and Mg supply - Guarçoni M., André (Coffee Science - ISSN 1984-3909, 2017)
The base saturation method (BSat), used to determining lime requirement (LR), may produce inadequate doses, since the expected base saturation (Ve) is fix, independently of the soil type. The aim of this work was to determine adequate expected base saturation (Ve) for the Arabica and Conilon coffee according to relationship between this characteristic, pH and Ca and Mg supply for the plants, in soils with different classes of cation-exchange capacity at pH 7 (T). Several chemical characteristics of 599 soil samples collected under coffee plantations were analyzed. Linear correlation analysis was performed, and selecting equations that best represent the relationship between pH and V. Base saturations were estimated that would be related to suggested pH values for the arabica and conilon coffees, as well as the adequate supply of Ca and Mg, considering soils with low, medium or good T. The relationship between pH and V was not linear. Take into account the same soil pH, V changing accordingly to T. It was recommended the following Ve values for coffee plantations, according to T classes: Ve = 90% (for low T: TL< 4,30cmolc dm-3), Ve = 70% (for medium T: 4,30 < TM < 8,60 cmolc dm-3) and Ve = 60% (for good T8,60 <TG< 15,00 cmolc dm-3).